Achieving Efficient NIR‐II Type‐I Photosensitizers for Photodynamic/Photothermal Therapy upon Regulating Chalcogen Elements. Issue 7 (5th January 2022) - Wen, Kaikai; Tan, Hui; Peng, Qian; Chen, Hao; Ma, Han; Wang, Lu; Peng, Aidong; Shi, Qinqin; Cai, Xiaodong; Huang, Hui
Abstract: Second near‐infrared (NIR‐II) window type‐I photosensitizers have intrinsic advantages in photodynamic/photothermal therapy (PDT/PTT) of some malignant tumors with deep infiltration, large size, complicated location, and low possibility of surgery/radiotherapy. Herein, three chalcogen‐element‐based donor–acceptor‐type semiconducting polymers (poly[2, 2″‐(( E )‐4, 4″‐bis(2‐octyldodecyl)‐[6, 6″‐bithieno[3, 2‐ b ]pyrrolylidene]‐5, 5″(4 H, 4″ H )‐dione)‐ alt ‐2, 5‐(thiophene)] (PTS), poly[2, 2″‐(( E )‐4, 4″‐bis(2‐octyldodecyl)‐[6, 6″‐bithieno[3, 2‐ b ]pyrrolylidene]‐5, 5″(4 H, 4″ H )‐dione)‐ alt ‐2, 5‐(selenophene)] (PTSe), and poly[2, 2″‐(( E )‐4, 4″‐bis(2‐octyldodecyl)‐[6, 6″‐bithieno[3, 2‐ b ]pyrrolylidene]‐5, 5″(4 H, 4′ H )‐dione)‐ alt ‐2, 5‐(tellurophene)] (PTTe)) are synthesized and fully characterized, demonstrating strong absorption in the NIR‐II region. Upon adjusting the chalcogen elements, the intramolecular charge‐transfer characteristics and the heavy‐atom effect are tuned to enhance the intersystem crossing rate, improving the photodynamic effect. Moreover, the energy levels and Gibbs free energies are tuned to facilitate the type‐I photodynamic process. As a result, PTTe nanoparticles (NPs) produce superoxide anion radicals (O2 − ) more efficiently and demonstrate higher photothermal conversion efficiency than PTS and PTSe NPs upon NIR‐II (1064 nm) laser irradiation, exhibiting unprecedented NIR‐II type‐I PDT/PTT performance in vitro and in vivo. This work provides ideas for achieving high‐performance NIR‐II type‐I PDT/PTT semiconducting polymers for hypoxic oncotherapy. Abstract : Second near‐infrared (NIR‐II) window semiconducting polymers (SPs) for type‐I photodynamic therapy (PDT) through generating O2 − for hypoxic oncotherapy have not previously been reported. Upon tuning of chalcogen elements, the first type‐I PDT NIR‐II SPs are achieved due to narrowed Δ E ST and enlarged spin–orbit coupling constant. The suitable lowest unoccupied molecular orbital energy and Δ G  < 0 provides ideas for designing type‐I photosensitizers.